Contact Modulation Using Pulsed Thermal Annealing in 2-Dimensional Semiconductors - Alolaiyan, Olaiyan; Alhazmi, Abrar; Alghamdi, Saeed; Alamri, Faisal; Alhamdan, Khalid; Alsulami, Awsaf; Amer, Moh. R. (2021 IEEE 16th Nanotechnology Materials and Devices Conference (NMDC), 2021)
2-Dimensional (2D) materials have been the subject of intensive research for electronic and photonic applications. Yet, the realization of a "good" ohmic contact with 2D materials is still a major hurdle that requires focused investigations. Metal deposition methods have proven to alter the electronic behavior of 2D materials, which can introduce defects and opens scattering paths for carriers. Here, we demonstrate new technique that can modulate contact resistance of the 2D material with the source and drain electrodes using MoS 2 transistors. Exfoliated 2D Nanosheets are micro-aligned and deposited on prefabricated metal electrodes. Before any treatment, devices show poor electrical performance with high device resistance which is caused by weak contact between the 2D nanosheet and the metal electrodes. However, after applying a pulsed thermal annealing treatment with a short time interval, we notice a remarkable enhancement in IV_{ds} and IV_{gs} properties. For MoS 2 transistors, we notice the maximum enhancement occurring after the first treatment. Our treatment can be a promising technique to create high performance electronics for device applications.